IMPLEMENTASI PEMBENTUKAN KARAKTER MANDIRI MELALUI PEMBELAJARAN TEMATIK KELAS RENDAH MADRASAH IBTIDAIYAH - Ira Wahyuni; Devi Wahyu Ertanti; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
In the world of education, it is not only educating students to know the material or knowledge, but also being educated so that good character is formed in students. There are several values of character education that must be instilled and developed in students, one which is the value of independent character education. This study aims to describe and analyze planning and implementation in the formation of independent characters through thematic learning, as well as the factors that influence the formation of independent characters. The approuch used in this research is a qualitative approach with the type of case study research using 3 techniques in data collection, namely observation, interviews and documentation. Independent character education can be implemented through learning activities in the classroom, one of which can be done by teachers through the learning process, especially thematic learning. In the thematic learning there are many activities that shape the independent character of students, because one of the characteristics of thematic learning is student-centered so that students are required to be active in learning. Key word: character building, independent, thematic learning